(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the influence of the English language on modern toponyms in Uzbekistan. It highlights how, as a result of globalization, tourism, and economic expansion, English-language names such as “Green Park” and “New City” have become popular in newly developed metropolitan areas. The paper explores the reasons behind this trend—such as the pursuit of modernism and global appeal—and discusses its impact on regional cultural identity and traditional naming conventions.